2008
DOI: 10.1088/0741-3335/50/9/095002
|View full text |Cite
|
Sign up to set email alerts
|

Current drive by EC waves in the presence of magnetic islands and transport

Abstract: In this paper we address the problem of current drive by electron cyclotron (EC) waves in the presence of magnetic islands and transport. Our approach makes use of quasilinear theory by numerically solving the Fokker-Planck equation in cylindrical geometry. We take into account the actual geometry of the islands along the calculations as well as the changes in the plasma density profile due to the action of the radial particle transport. The particle transport is supposed to have a magnetic origin. The waves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…For example, under some conditions, the cross-field heat conductivity has been found to be strongly reduced inside the island [30,31]. Theoretical and numerical works have shown that the different magnetic topologies due to the presence of a magnetic island can have important consequences for the flux-surface averaged quasilinear diffusion and the consequent power density deposition profile as well as drive current density profile [32][33][34]. These points will be the subject of future work.…”
Section: Discussionmentioning
confidence: 91%
“…For example, under some conditions, the cross-field heat conductivity has been found to be strongly reduced inside the island [30,31]. Theoretical and numerical works have shown that the different magnetic topologies due to the presence of a magnetic island can have important consequences for the flux-surface averaged quasilinear diffusion and the consequent power density deposition profile as well as drive current density profile [32][33][34]. These points will be the subject of future work.…”
Section: Discussionmentioning
confidence: 91%
“…The main effect of the presence of islands is the reduction in the area of the magnetic surface where the wave power is deposed and a consequent increase in the EC power density over the resonant surface as compared with the case without islands. At a steady state, the value of the current density is proportional to the ratio between the area of the resonant surface in the case without the perturbation and the area of the surface near the islands' centre [7].…”
Section: Introductionmentioning
confidence: 99%
“…The explicit form of the different coefficients appearing in the equation ( 6) may be found in the literature (for example, [16]).…”
Section: The Fokker-planck Equation and Numerical Schemementioning
confidence: 99%